Digital Power and Religious Resistance: Analyzing LGBT Content on Ragil Mahardika’s YouTube Channel through Michel Foucault’s Framework - Latif, Jamilul; Moh Asror Yusuf (Journal of Islamic Philosophy and Contemporary Thought, 2023)
The phenomenon of LGBT content on Ragil Mahardika’s YouTube channel has sparked various reactions in Indonesian society, particularly on social media. This article aims to examine this content from a religious perspective and analyze it using Michel Foucault’s concept of power. Through a qualitative approach based on literature review and critical discourse analysis, this study finds that Ragil utilizes social media to build legitimacy for the LGBT community in Indonesia, employing power strategies involving normalization, regulation, production, and diffusion of influence. The findings indicate that power is not only repressive but also productive, reflected in content production and the formation of public opinion. However, religious responses—particularly from Islam—function as a form of resistance against normalization efforts, affirming that religious teachings remain an ideological force that rejects LGBT behavior. This study emphasizes the dynamic relationship between digital content, power, ideology, and resistance. Therefore, strengthening religious understanding among the younger generation is necessary to maintain the integrity of moral values amid the rapid flow of global information.